1997
DOI: 10.1093/carcin/18.7.1291
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1-induced DNA adduct formation and p53 mutations in CYP450- expressing human liver cell lines

Abstract: Epidemiological evidence has been supporting a relationship between dietary aflatoxin B1 (AFB1) exposure, development of human primary hepatocellular carcinoma (HCC) and mutations in the p53 tumor suppressor gene. However, the correlation between the observed p53 mutations, the AFB1 DNA adducts and their activation pathways has not been elucidated. Development of relevant cellular in vitro models, taking into account species and tissue specificity, could significantly contribute to the knowledge of cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(119 citation statements)
references
References 10 publications
5
112
0
2
Order By: Relevance
“…In vitro studies exposing human liver cell lines to AFB 1 presented the same 249 ser mutational pattern of TP53 (Aguilar et al, 1993;Mace et al, 1997), as it has been reported in the epidemiological studies ( Figure 1c). There are at least two possible explanations for these findings.…”
Section: Aflatoxin Bsupporting
confidence: 77%
“…In vitro studies exposing human liver cell lines to AFB 1 presented the same 249 ser mutational pattern of TP53 (Aguilar et al, 1993;Mace et al, 1997), as it has been reported in the epidemiological studies ( Figure 1c). There are at least two possible explanations for these findings.…”
Section: Aflatoxin Bsupporting
confidence: 77%
“…THLE cells, obtained by transfection of the simian virus 40 large tumor antigen gene into primary hepatocytes (Pfeifer et al, 1995), did not express several important P450 isoenzymes, but clones expressing CYP3A4 (T5-3A4) or CYP2D6 (T5-2D6) were produced by subsequent transfection (Mace et al, 1997). Cell-culturing details are presented elsewhere (Molden et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…These compounds are immunosuppressive, carcinogenic, teratogenic and mutagenic, and acute exposure to high levels of aflatoxin leads to aflatoxicosis, which can result in rapid death from liver failure. Symptoms of acute aflatoxicosis include, but are not limited to, swollen stomach, fatigue, swollen legs, and eyes turning yellowish [11,12]. In 2004, during the worst known outbreak of aflatoxicosis in Kenya, 317 cases were reported of which 125 died [13].…”
Section: Introductionmentioning
confidence: 99%